Beliefs as a Means of Self-Control? Evidence from a Dynamic Student Survey - Tobias König; Sebastian Schweighofer-Kodritsch; Georg Weizsäcker (Ludwig-Maximilians-Universität München und Humboldt-Universität zu Berlin, Collaborative Research Center Transregio 190 - Rationality and Competition, 2018)
We repeatedly elicit beliefs about the returns to study effort in a panel survey of students of a large university course. A behavioral model of quasi-hyperbolic discounting and malleable beliefs yields the prediction that the dynamics of return beliefs mirrors the importance of exerting self-control, such that return expectations first increase as the exam approaches, and then sharply drop post-exam. Exploiting variation in exam timing to control for common information shocks, we find this prediction confirmed: average subjective expections of returns increase by about 20% over the period before the exam, and drop by about the same amount afterwards.
Keywords: D90; I26; 330; belief elicitation; return to study effort; dynamic belief patterns